An Analysis of Idiomatic Expressions Found in Adele’s Selected Lyrics Songs - Revalda Yalase; Siti Aisyah (STKIP PGRI SIDOARJO, 2022)
This study is being carried out in attempt to discover the idiomatic terms utilized in the songs of Adele. This study employed qualitative research that focused on content or document analysis. In this study, the songs from Adele were used as the data source. Makkai's theory was used to the data analysis (1972). The researchers searched the internet for the music album, looked for the script lyrics, listening, and typing. Beyond that, data analysis included reading, evaluating, recognizing, and classifying the sorts of idiomatic idioms present in song lyrics, and finally making conclusions. After evaluating the data, the researchers discovered three idiomatic phrases portrayed in the lyrics of the songs: phrasal verb idioms, tournure idioms, and incorporating verb idioms. Keywords : idioms,song lyrics,Adele